Tvorba webové prezentace firmy - Horna, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Moje práce se zabývá návrhem internetových stránek pro propagační účely firmy. Obsah práce je zaměřen na celkový proces tvorby webových stránek od zahájení a zpracování projektu, přes tvorbu stránek až po jejich doladění a předání. Hlavní důraz při tvorbě je kladen na marketingové využití stránek.

My work put mind to project of Internet pages for firm promotional purpose. Content of my work is intent on overall process of web pages creation from opening to project processing, through creation of pages after as much as their finish and assignment.The main accent throughout creation is accentuate for marketing usage.
Creation of web presentation for company
Keywords: Internet; webové stránky; propagace firmy; návrh projektu; tvorba webu; marketingová podpora; architektura webu; design a navigace; optimalizace pro vyhledávače; Internet; web pages; firm promotion; project propsal; web creation; marketing support; web architecture; design and navigation; optimalization for locators